Optimising resources in management of maintenance : a study using electrical (building) services. - Chian, Thian Shian. (2009)
This project explores the subject "Management of Maintenance" and its use in property valuation and management. A 3-E model (ie. Expectation; Enhancement; and Element) is used for classifying the various methods of computing and allocating maintenance budget. The model provides a structured approach useful for an investor to project and control their maintenance cashflow to avoid cash over run. However, the current methods are unable to address the pressing resource wastage currently faced by management (or building's owner). Therefore an enhanced framework is proposed. Based on this enhanced framework, a workshop was conducted to structure and represent the knowledge of maintenance (electrical) faults. A three-months field trial followed and its data subsequently analyzed. Findings reveal the usefulness of this enhanced framework and its significant value when used within the 3-E model for an investor (or a building's owner) to compute, monitor and control the maintenance budget to achieve cost-effectiveness.